Human amniotic membrane dressing for the treatment of an infected wound due to an entero-cutaneous fistula: Case report. (2018) - Barski, Dimitri; Gerullis, Holger; Ecke, Thorsten; Varga, Gabriella; Boros, Mihaly; Pintelon, Isabel; Timmermans, Jean-Pierre; Otto, Thomas
Highlights: HAM can be a useful, potential scaffold for treatment of infected, irregular, deep wounds due to the promotion of epithelial regeneration, elastic and antibacterial characteristics. Clinical case of chronic wound with an entero-cutaneous fistula was successfully treated with HAM dressings after 8 weeks. Histological analysis showed partial re-epithelialisation and muscle cells recovery 4 weeks after the treatment. The preliminary results support the initiation of prospective trial and registry according to IDEAL. Abstract: Introduction: Infected wounds are difficult to treat and there are no standardized protocols. Presentation of case: We report a case of infected postoperative wound and entero-cutaneous fistula in a 83 years-old woman. An innovative treatment protocol for Human amniotic membrane (HAM)-assisted dressing of infected wound as the Idea Stage following the IDEAL recommendations is presented. The development of amnion preparation and the involved treatment steps are described. No adverse events and no graft rejection have been detected. Discussion: Favorable results confirm the technical simplicity, safety and efficacy of this procedure. HAM has been shown to promote wound healing and to have antibacterial characteristics, which was supported by the presented case. Conclusion: We are able to report a successful treatment of an infected wound caused by entero-cutaneous fistula with HAM dressing. Following the IDEAL recommendations, consecutive prospective cohort trials are justified.